Implementation of Electronic Signature Policy in Bogor Regency Government Apparatus - WIDYARTAMA, ARISKI WIRA; SOFIANA HERMEILITHA; ASROPI (Universitas Pancasakti Tegal, 2024)
Electronic Signatures are a form of e-Government implementation in government, influenced by various factors that have a crucial role in this policy. This research aims to analyze the implementation of the Electronic Signature policy based on Bogor Regent Regulation Number 77 of 2021 concerning the Management of the Use of Electronic Certificates within the Bogor Regency Government. Based on the theory of George C. Edward III (1980), four variables determine the success of implementing the policy in question. The method used is a qualitative method through in-depth interviews with several sources, including the Bogor Regency Diskominfo Encryption Section, Bogor Regency BPKAD Treasury Officials, and the General and Personnel Subdivision (Umpeg) at the Bogor Regency Disdukcapil. The research results show that the four variables influence the success of implementing the policy. This policy has been communicated to all regional officials in Bogor Regency, ensuring that resources such as the number of employees and server facilities play a vital role in the successful implementation of the policy. Employees who understand the use of Electronic Signatures, supported by adequate server facilities, are the key to the smooth implementation of this policy. The regional head, through a regent's regulation, explained that the main aim of implementing this policy is to achieve time and cost efficiency, hoping to increase work effectiveness and efficiency. This research uses qualitative methods with data collection through in-depth interviews as the primary source of information.